2016
DOI: 10.1007/s13337-016-0331-y
|View full text |Cite
|
Sign up to set email alerts
|

First report of hepatitis E virus viremia in healthy blood donors from Nepal

Abstract: The aim of this study was to detect the prevalence of hepatitis E virus (HEV) in healthy blood donors so as to decipher the maintenance of (HEV) reservoir if any. Five hundred and eighty-one blood samples along with clinical information were collected from central blood bank, Kathmandu between February and March 2014. Samples were tested for hepatitis B virus surface antigen, anti-hepatitis C virus antibodies, anti-hepatitis A virus IgM, HEV antigen, HEV viral load and anti-HEV antibodies (IgM and IgG) by ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
2
14
0
1
Order By: Relevance
“…Similarly, Zhang et al have reported that the majority of HEV infections in RNA‐positive donors in China were attributed to genotype 1 (19/33 = 58%) and genotype 4 (14/33 = 42%). In a similar line, Gupta et al had reported hepatitis E viremia in healthy blood donors in Nepal for the first time in 2016, where seven of 27 anti‐HEV IgM‐positive donors were found HEV RNA positive belonging to genotype 1.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, Zhang et al have reported that the majority of HEV infections in RNA‐positive donors in China were attributed to genotype 1 (19/33 = 58%) and genotype 4 (14/33 = 42%). In a similar line, Gupta et al had reported hepatitis E viremia in healthy blood donors in Nepal for the first time in 2016, where seven of 27 anti‐HEV IgM‐positive donors were found HEV RNA positive belonging to genotype 1.…”
Section: Discussionmentioning
confidence: 69%
“…The seroprevalence rates in many European countries ranging from 1.3% to 52% have been reported. Similarly, seroprevalences of HEV in blood donors ranging from 1.8% to 9.8% in South America, 3.4% to 30% in several Asian countries have been reported. The current study from India, a developing country, showing a prevalence rate of 17.70% goes at par with rates reported in several Asian countries attributing to similar endemicity of HEV infection.…”
Section: Discussionmentioning
confidence: 81%
“…On review of full‐text articles for the remaining 140 citations, 83 did not meet selection criteria. Of the 57 citations selected for final data synthesis , one provided three data sets ; hence, we had a total of 59 data sets from 28 countries (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…A large majority of data sets were from Europe, high or high‐middle income countries in Asia and North America (27, 12 and 4 data sets, respectively); by comparison, there were only eight studies from low/low‐middle income countries of Asia and Africa; the remaining eight data sets were from other parts of the world. In 39 data sets, all the blood units had been tested for HEV RNA, whereas in 20 data sets, the blood units were first screened for the presence of anti‐HEV antibodies ( n = 17) or for elevated serum ALT levels ( n = 3) , with only the screen‐positive units being tested for HEV RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the case fatality rate is very high projecting 16-38% among pregnant women as a result of, unexplainably high rate of fulminant hepatic failure, in comparison to general population curtailing to 1-3% [7]. The increasing reports of HEV being transmitted through blood transfusion also highlights the potential risk, this virus poses to blood supply safety [13,14]. However, screening for acute HEV infection serologically or HEV RNA is not routinely performed in Nepalese hospitals for any clinical procedures-blood transfusion or surgery.…”
Section: Introductionmentioning
confidence: 99%